2019
DOI: 10.1186/s12887-019-1841-8
|View full text |Cite
|
Sign up to set email alerts
|

Vocal and motor behaviors as a possible expression of gastrointestinal problems in preschoolers with Autism Spectrum Disorder

Abstract: BackgroundGastrointestinal (GI) problems are one of the most frequent comorbidities in Autism Spectrum Disorder (ASD) but can be under-recognized due to the concomitant communication difficulties of this population. Accordingly, some associated behaviors (AB) such as verbal and motor behaviors (VB and MB, respectively) have been identified as a possible expression of an underlying GI problem and evaluated through an ad hoc questionnaire (the Associated Behaviors Questionnaire -ABQ-). The aims of this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…As far as the CD clinical presentation in children with ASD, our results support a frequent asymptomatic form, which could be partially ascribed to the communication difficulties and the atypical sensory processing characteristic of ASD subjects, which in turn prevent the effective communication and/or the proper localization of GI symptoms [ 20 , 54 , 55 , 56 ]. Within this framework, we must be aware that GI symptoms can occur with sudden irritability or aggressive behavior in non-verbal children with ASD [ 20 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As far as the CD clinical presentation in children with ASD, our results support a frequent asymptomatic form, which could be partially ascribed to the communication difficulties and the atypical sensory processing characteristic of ASD subjects, which in turn prevent the effective communication and/or the proper localization of GI symptoms [ 20 , 54 , 55 , 56 ]. Within this framework, we must be aware that GI symptoms can occur with sudden irritability or aggressive behavior in non-verbal children with ASD [ 20 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 57%
“…Regarding ASD, the American Academy of Pediatrics recommends that every ASD child with GI symptoms should be evaluated with specific exams testing the GI tract [ 19 ]. Pediatricians often have difficulty recognizing signs of GI problems [ 20 ] and completing a medical examination that includes an accurate evaluation and follow-up of corporeal and weight - for - height development because of the frequent difficulty in visiting children with ASD and communication barriers typical of these patients. For these reasons, it could be very useful in the ASD population for the first step of screening for CD to be a blood sample analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is contradictory evidence regarding whether the prevalence of GIS differs according to gender. Several studies have reported no significant differences in gender, for children with and without GIS [ 48 , 49 , 50 ]. However, other studies have reported gender differences in the frequency of GIS.…”
Section: Resultsmentioning
confidence: 99%
“…Motor behaviours associated with the presence of GI disorders include seeking belly pressure, some pointing behaviours, neck or body posture, certain repetitive behaviours, aggressive or self-injurious behaviours. There is a strong correlation between aggressive behaviours and underlying GI disorders[ 42 ].…”
Section: Gi Disordersmentioning
confidence: 99%